Cognitive impairment with Type 2 Diabetes Mellitus among community-dwelling older adults in Chile: Prevalence, risk factors and cognitive characteristics - Bozanic, Agnieszka; Toro, Pablo; Bello-Lepe, Sebastián; Hurtado-Oliva, Javier; Beyle, Christian; Valdés, Catalina; Formiga, Francesc (Frontiers in Human Neuroscience, 2023)
Introduction: The aim of this study is to determine prevalence and risk factors of Cognitive Impairment (CI) and its association with Type 2 Diabetes Mellitus (T2DM) in subjects aged 65 years and above. Additionally, we attempt to provide a cognitive profile for T2DM group. Methodology: A cross-sectional analytical study to assess CI was carried out. We evaluated a sample of community-dwelling residents from Chile. All participants underwent a general interview, lifestyle questionnaires and a comprehensive neuropsychological battery. Regression analyses were performed to evaluate risk of CI with T2DM and influencing factors. Results between groups in the different domains of the neuropsychological assessment were compared by Student's t-tests and MANOVA. Results: Among all 358 subjects, overall T2DM prevalence were 17.3%. The prevalence of CI was higher in T2DM group compared to the healthy participants (30.7%, p<0.001). The risk of CI was 2.8 times higher in older people with T2DM compared to older people without the diagnosis. Multiple regression analysis, adjusted for age and gender, demonstrated that age, education, presence of dyslipidemia, and T2DM duration were the predictor variables significantly associated with CI. T2DM group performed worse on global cognitive performance, attention, language, verbal memory, visual memory, visual constructional ability, and executive function. After adjusting for significant covariates from multiple regression analysis, a relationship between “cognition” and T2DM is still observed. Amnesic multi-domain impairment was the specific cognitive identified pattern for T2DM group. Conclusions: The present study confirms the high prevalence of CI with T2DM among Chilean older adults in a community-based population. T2DM is significantly associated with a higher risk of CI, and age, education, presence of dyslipidemia, and duration of T2DM are risk factors. T2DM patients with CI are impaired in multiple cognitive domains, even after adjusting covariables, resulting in an amnesic multi-domain cognitive profile.